ICC assessment – experiences and perspectives. - Owczarek, Dorota (Glottodidactica, 2016)
The paper presents theoretical considerations on the role of dialogue in ICC development and assessment and the model for ICC assessment as a practical application. It is argued here that the application of the idea of dialogue in a Bakhtinian sense may constitute a theoretical framework for ICC assessment since this kind of dialogue involves the presentation of a variety of opinions or ideas. The model for ICC assessment, as it was developed for the purpose of the author’s unpublished PhD dissertation, is presented in this paper. The model includes various types of tests that can be incorporated into ICC evaluation. The final part of the discussion attempts at showing the points of convergence between DA approach and the dialogic approach to ICC assessment.